1990
DOI: 10.1161/01.res.67.4.844
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the spatial dispersion of acetylcholine release on the chronotropic responses to vagal stimulation in dogs.

Abstract: We determined the effects of changing the spatial dispersion of acetylcholine release on the phase-dependent chronotropic responses to vagal stimulation in anesthetized dogs. We stimulated the vagus nerves with one brief burst of electrical pulses each cardiac cycle, and we changed the timing of the stimulus by a small, constant amount each cardiac cycle to scan the entire cycle. To vary the heterogeneity of acetylcholine release, we changed the voltage of the stimulus pulses over a range of submaximal values.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Previous studies have reported on considerable reductions in the responsiveness of the cardiac pacemaker to vagal chronotropic effects after small changes in the timing of vagal stimulation over a certain specific phase of the cardiac cycle [25,[43][44]. In the present study, when a vagal burst of six pulses was delivered at 180-200 ms before the next P wave of the ECG, a small (∼25 ms; Fig.…”
Section: Effects Of Subtype-selective Muscarinic Cholinoreceptor Blocsupporting
confidence: 42%
See 4 more Smart Citations
“…Previous studies have reported on considerable reductions in the responsiveness of the cardiac pacemaker to vagal chronotropic effects after small changes in the timing of vagal stimulation over a certain specific phase of the cardiac cycle [25,[43][44]. In the present study, when a vagal burst of six pulses was delivered at 180-200 ms before the next P wave of the ECG, a small (∼25 ms; Fig.…”
Section: Effects Of Subtype-selective Muscarinic Cholinoreceptor Blocsupporting
confidence: 42%
“…First, changes in the timing of vagal stimulation throughout the cardiac cycle produce variations in effective concentrations of acetylcholine at the sinoatrial node due to rapid hydrolysis by acetylcholinesterase [10][11]. Because of the short half-life of neurally released acetylcholine in the cardiac neuroeffector junction [10,27,35], a vagal burst delivered at a short P-Stimulus interval over the initial portion of the cardiac cycle produces a chronotropic response that is of a lower magnitude as compared to those elicited by vagal bursts applied at progressively later periods [25,20,[43][44]. This is consistent with results of the present study (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations